A Critical Analysis of Sayyid Husain al-Ṭabāṭabā’i’s Thoughts on Mut’ah Marriage in The Book of Tafsīr al-Mīzān - Faizal, Liky; Qohar, Abd.; Wahid, Ali Abdul; Rofi'i, Hilmi Yusron (Universitas Islam Negeri Raden Intan Lampung, 2024)
This article discusses Sayyid Husain al-Ṭabāṭabā’i's thoughts on mut'ah marriage (contract marriage) in his book Tafsīr al-Mīzān. The aim is to gain a broader understanding that can be used as material in preparing better legislative regulations. This research is descriptive library research, using secondary data sources in the form of primary and secondary legal materials. The results of the study show that according to al-Ṭabāṭabā'i, mut'ah marriage is a legal marriage, as explained in Tafsīr al-Mīzān, where the word istamta'tum refers to the term mut'ah marriage. However, the MUI fatwa states that the mut'ah contract is not a valid marriage and is contrary to the laws and regulations in Indonesia. The MUI considers mut'ah marriage to be something that does not follow Sharia principles. Therefore, to prohibit the practice of mut'ah marriage in Indonesia, it is recommended that there be changes to Article 2 of Law Number 1 of 1974 concerning Marriage to read: